Analysis Of Raw Material Supply In The Mak Sulis Business In Bengkulu City - Tifani Rika Amelya; Sulisti Afriani; Nenden Restu Hidayah (Penerbit Jurnal Indonesia, 2024)
Considering the importance of raw material inventory in business operations, a company needs to manage raw materials in a controlled manner. The main raw material used is wheat flour. In the production of bread, wheat flour is the main raw material which must always be available for the smooth production process, therefore it is necessary to carry out appropriate control and planning in the supply of the raw material for this flour. Therefore, the researcher is interested in conducting research with the title